A audiência pública jurisdicional no estado constitucional: uma análise crítica das audiências públicas realizadas pelo Supremo Tribunal Federal - Backes, Maria Helena (Universidade do Vale do Rio dos Sinos, 2014)
Within the Brazilian constitutional jurisdiction, the role of the Supreme Court is increasingly valued, publicized and also questioned. This is because, in the analysis and judgment of social (and procedural) demands with public interest and general implications, is that Court who takes upon society, the major responsibility for a final decision and the formulation of new models and judicial parameters for a response to social unrest. By this way, public audiences emerge as a tool to contribute to the formation of decision-making, from discussion and clarification on certain subject, enabled through the participation of interested civil society. Considering this premise, the present study arises from the concern, in a critical way, evaluate the purposes and methods undertaken by the Brazilian Supreme Court through public audiences, in the sense that their results provide generation of based and legitimate democratic constitutional decisions in the product of this movement and encounter between the judiciary and civil society that is historically structured by sociological worries about justice access. For this purpose, it was necessary the development of three chapters. In the first, the study presents the historical and legal source of public audiences, analyzed from their various purposive reasons identified by Brazilian law, in its various contexts. The second chapter is formed from the observation on the development of the Justice Access as a fundamental right, the growing judicialization of social demands, kept as a great post-modern effect of the conjunction by democracy concepts and popular participation in the context established by the current Brazilian legal scenario. Finally, the third chapter shows the analysis on each of the public hearings held by the Supreme Court until then, and judicial decisions, considered the final product of participatory interaction between the Supreme Court and civil society. This study attends the research line in Hermeneutics, Constitution and Implementation of Rights and is anchored in public law, the concentration area of the post Graduate Program in Law, Universidade do Vale do Rio dos Sinos - UNISINOS therefore focuses on the effective realization of rights through legal instruments adopted within the constitutional jurisdiction and its effective response to social provocations.
Keywords: Acesso à justiça; Audiências públicas; Jurisdição constitucional; Democracia; Sociedade; Supremo tribunal federal; Access to justice; Public hearing; Constitutional jurisdiction; Democracy; Society; Supreme court; ACCNPQ::Ciências Sociais Aplicadas::Direito